istians in the Nicaraguan revolution/ Margaret Randall - dall, Margaret|Ch (Estados Unidos de América : New Star Books)
In Nicaragua, for the first time in modern history, the official church sided with an authentic popular revolution.
Nicaragua History 2. Revolution
. Educ
Keywords: HISTORY - REVOLUTION OF NICARAGUA 2. RELIGION AND POLITICS - NICARAGUA 3. LIBERATION THEOLOGY|Co